Rekonseptualisasi Seleksi Hakim Konstitusi Sebagai Upaya Mewujudkan Hakim Konstitusi yang Berkualifikasi - Indramayu, Indramayu; Jayus, Jayus; Indrayati, Rosita (University of Jember, 2017)
Integrity, good character, justice, and expert statesman of the constitution as the indicators to appoint Constitutional Judge should be taken into account by the Supreme Court, the House, and the President in the selection process. The cases of corruption named Akil Mochtar and Patrialis Akbar as the convicted and the suspected persons respectively should be regarded as an appropriate opportunity to evaluate law relating to the Constitutional Judges selection process in which it is not clearly defined in the Constitutional Court Act. To date, the law relating to selection is given to respective institutions where the Supreme Court takes the selection internally with no transparency, the House only requires to write and present article, and—in some cases—the President prefers to appoint with no adequate criteria. The article uses doctrinal research in addressing the case related to the current regulation on constitutional judge selection. It concludes that the Supreme Court, the House, and the President ignore the principles of transparency, participatory, objectivity, and accountability in the selection, including the possibility of resulting unqualified judge. The selection needs reconceptualization comprising the establishment of expert panel, unaffiliated candidate to a political party, and re-concept of selection mechanism. Keywords: Reconceptualization, Selection, Constitutional Judge